Comparison of Different Blood Lactate Threshold Concepts for Constant Load Performance Prediction in Spinal Cord Injured Handcyclists - Stangier, Carolin; Abel, Thomas; Zeller, Sebastian; Quittmann, Oliver Jan; Perret, Claudio; Strüder, Heiko K. (Frontiers in Physiology, 2019)
Background Endurance capacity is one of the main performance determinants in handcycling. There are two exercise test procedures primarily applied to determine endurance capacity, to verify training adaptations and predict race performance. This study aims to evaluate the agreement of these applied concepts in handcycling. Methods In a repeated measures cross-over design, 11 highly trained male spinal cord injured (Th12 to L1) handcyclists (age: 40 ± 9 years, height: 183 ± 8 cm, body mass: 73.2 ± 8.5 kg) performed a graded exercise test (GXT) and a lactate minimum test (LMT) to determine lactate threshold at 4 mmol L–1 (LT4 mmol L−1) and lactate minimum (LM), respectively. The agreement of both lactate thresholds concepts for constant load performance prediction (change of ≤ 1 mmol L–1 during the last 20 min) was evaluated within constant load tests (CLT; 30 min) at a power output (PO) corresponding to LT4 mmol L–1 and LM. Oxygen uptake (V.⁢O2), respiratory exchange ratio (RER), heart rate (HR) and blood lactate (La) were measured during all tests. Results Power output at the corresponding thresholds (LT4 mmol L−1: 149 ± 34 W vs. LM: 137 ± 18 W) revealed no significant difference (p = 0.06). During the CLT at LT4 mmol⋅L−1 and LM, V.⁢O2, and RPE were not significantly different. However, LA, RER, and HR were significantly higher (p ≤ 0.02) during CLT at LT4 mmol L−1. Bland–Altman plots indicate a wide range of dispersion for all parameters between both lactate threshold concepts. Evaluations of LT4 mmol L−1 and LM did not meet the criteria for constant load performance within the CLT for 33 and 17% of the athletes, respectively. Discussion Both exercise tests and the corresponding lactate threshold concept revealed appropriate estimates to predict a steady state performance for the majority of participants. However, as PO determination at LT4 mmol L−1 and LM exceeds the criteria for constant load performance (increase of ≥ 1 mmol L–1) for 33 and 17% respectively the current results indicate the common criteria for constant load performance (change of ± 1 mmol L–1) might not be sufficiently precise for elite athletes in handcycling. Consequently, exercise test results of elite athletes should be analyzed individually and verified by means of several CLT.